"Well, not me, but other women do not register because..."- Barriers to seeking antenatal care in the context of prevention of mother-to-child transmission of HIV among Zimbabwean women: a mixed-methods study - Euphemia L. Sibanda; Sarah Bernays; Ian V. D. Weller; James G. Hakim; Frances M. Cowan (BMC, 2018)
Abstract Background While barriers to uptake of antenatal care (ANC) among pregnant women have been explored, much less is known about how integrating prevention of mother-to-child transmission (PMTCT) programmes within ANC services affects uptake. We explored barriers to uptake of integrated ANC services in a poor Zimbabwean community. Methods A cross-sectional survey was conducted among post-natal women at Mbare Clinic, Harare, between September 2010 and February 2011. Collected data included participant characteristics and ANC uptake. Logistic regression was conducted to determine factors associated with ANC registration. In-depth interviews were held with the first 21 survey participants who either did not register or registered after twenty-four weeks gestation to explore barriers. Interviews were analysed thematically. Results Two hundred and ninety-nine participants (mean age 26.1 years) were surveyed. They came from ultra-poor households, with mean household income of US$181. Only 229 (76.6%) had registered for ANC, at a mean gestation of 29.5 weeks. In multivariable analysis, household income was positively associated with ANC registration, odds ratio (OR) for a $10-increase in household income 1.02 (95% confidence interval, CI, 1.0-1.04), as was education which interacted with having planned the pregnancy (OR for planned pregnancy with completed ordinary level education 3.27 (95%CI 1.55-6.70). Divorced women were less likely to register than married women, OR 0.20 (95%CI 0.07-0.58). In the qualitative study, barriers to either ANC or PMTCT services limited uptake of integrated services. Women understood the importance of integrated services for PMTCT purposes and theirs and the babies' health and appeared unable to admit to barriers which they deemed "stupid/irresponsible", namely fear of HIV testing and disrespectful treatment by nurses. They represented these commonly recurring barriers as challenges that "other women" faced. The major proffered personal barrier was unaffordability of user fees, which was sometimes compounded by unsupportive husbands who were the breadwinners. Conclusion Women who delayed/did not register were aware of the importance of ANC and PMTCT but were either unable to afford or afraid to register. Addressing the identified challenges will not only be important for integrated PMTCT/ANC services but will also provide a model for dealing with challenges as countries scale up 'treat all' approaches.